Metode Pembelajaran Tahfiz al-Quran di Pondok Pesantren Nurul Amal Kabupaten Ciamis Provinsi Jawa Barat - Daryaman Daryaman; Nurwadjah Ahmad EQ; Andewi Suhartini (Matan : Journal of Islam and Muslim Society, 2022)
The learning method has a very important position in teaching and learning activities because it is one of the main factors that determine the success of learning. This study aims to determine the method of learning tahfiz al-Quran (memorizing the Quran) at Pondok Pesantren Nurul Amal, Cijeungjing, Ciamis, West Java. This research is qualitative research and case study. The data were collected using observations, interviews, and documentation. The data were analyzed using the triangulation technique. The results showed that there were several methods of learning tahfiz al-Quran used at Pondok Pesantren Nurul Amal, namely the lecture method, setoran, question and answer, classical, and takrir (repetition) method. The educational values ​​that can be learned from these methods include 1) to achieve success in the process of memorizing the Quran, strong motivation is needed; 2) memorizing the Quran requires various methods; 3) success of tahfiz al-Quran requires a continuous process.